Optimization of Pb(II) removal using Magnetic y-Fe2O3/KCC-1 Synthesized from Palm Oil Fuel Ash - Lim, J.Q.; R. S. R., Mohd Zaki; S. N., Miskan; N. Aini, Razali; N. F., Jaafar (Universiti Malaysia Pahang, 2022)
The pollution of lead, Pb(II) in water bodies has severely threatened the environment and human health due to its toxicity. Thus, removing Pb(II) from water bodies is an imperative task. In this study, the removal of Pb(II) using magnetic y-Fe2O3/KCC-1 synthesized from Palm Oil Fuel Ash (POFA) was explored. The characterization analysis confirmed a successful preparation of y-Fe2O3/KCC-1 with BET surface area and pore volume of 401 m2g-1 and 0.90 cm3g-1, respectively. The optimization by response surface methodology (RSM) with independent variables of initial Pb(II) concentration (